PARADIGMA TAFSIR EKOLOGI - Saddad, Ahmad (IAIN Tulungagung, 2017)
This article will display a new model of Islamic interpretation. That new model is ecology?s form, it can be called by ecology interpretation. There are many paradigms of human relation with environment, even anthropocentrism, egocentrism or ecoteosentrism. The searching of ecology? verses and the example of ecology interpretation is the focus of this article. The ecology?s paradigm of interpretation is a new point of view (new paradigm) where an interpreter will conscript their pieces from ecology? point of view or perspective. So, their idea will show their support to ecology?s problems and want to give contribution and solution toward ecology?s problem which descended upon this modern society. Been inspirited from Rabbil Alamin ?term which was repeated 14 times in the holy qur?an, so ecology interpretation use ecoteocentrism paradigm. The ecology?s act is the reflection or manifestation of human trust? system which reside in their deepest heart. Therefore, if their trust? system pro-ecology, their wisdom toward environment is high. Besides, if the trust? system contra ?ecology, their wisdom toward environment is low or opposing environment. By using ecoteocentris paradigm, human relation with nature will be harmony. Because of the scarcity of that paradigm. By that paradigm, human have truly consciousness to protect environment. They will also have truly consciousness to responsibility about environment in front of the God Almighty. So the paradigm of ecology interpretation is very urgent to be growth and ever lasted. Keywords: interpretation, ecology, al-Qur?an, ecoteocentrism